Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(81-\left(3x+2\right)^2=9^2-\left(3x+2\right)^2=\left(9-3x-2\right)\left(9+3x+2\right)=\left(7-3x\right)\left(11+3x\right)\)
b) \(\left(7x-4\right)^2-\left(2x+1\right)^2=\left(7x-4-2x-1\right)\left(7x-4+2x+1\right)\)
\(=\left(5x-5\right)\left(9x-3\right)=15\left(x-1\right)\left(3x-1\right)\)
c) \(9\left(x-5y\right)^2-16\left(x+y\right)^2=\left[3\left(x-5y\right)-4\left(x+y\right)\right]\left[3\left(x-5y\right)+4\left(x+y\right)\right]\)
\(=\left(-x-19y\right)\left(7x-11y\right)\)
\(a,x^2+4x-y^2+4\)
\(=\left(x^2+4x+4\right)-y^2\)
\(=\left(x+2\right)^2-y^2\)
\(=\left(x+2-y\right)\left(x+2+y\right)\)
\(b,25-4x^2-4xy-y^2\)
\(=25-\left(4x^2+4xy+y^2\right)\)
\(=5^2-\left(2x+y\right)^2\)
\(=\left(5-2x+y\right)\left(5+2x+y\right)\)
\(c,x^3-x+y^3-y\)
\(=\left(x+y\right)\left(x^2-xy+y^2\right)-\left(x+y\right)\)
\(=\left(x+y\right)\left(x^2-xy+y^2+1\right)\)
\(a,x^2+7x+7y-y^2\)
\(=x^2-y^2+7\left(x+y\right)\)
\(=\left(x-y\right)\left(x+y\right)+7\left(x+y\right)\)
\(=\left(x+y\right)\left(x-y+7\right)\)
\(b,x^2-2x-9y^2+6y\)
\(=x^2-\left(3y\right)^2-2\left(x-3y\right)\)
\(=\left(x-3y\right)\left(x+3y\right)-2\left(x-3y\right)\)
\(=\left(x-3y\right)\left(x+3y-2\right)\)
\(c,x^2-xy+x^3-3x^{2y}+3x^{2y}-y^3\)
\(=x\left(x-y\right)+\left(x-y\right)\left(x^2+xy+y^2\right)\)
\(=\left(x-y\right)\left(x+x^2+xy+y^2\right)\)
a.\(27x^3+27x^2+9x+1=\left(3x+1\right)^3\)
b.\(x^3-6x^2+12x-8=\left(x-2\right)^3\)
c.\(8x^3+12x^2+6x+1=\left(2x+1\right)^3\)
b)x2(x+1)-(x+1)=(x+1)(x2-1)
d) 4x(x-2)-(x-2)=(x-2)(4x-1)
câu a bn ghi mik k hỉu
a ) \(4x^2-y^2+4x+1\)
= \(\left(4x^2+4x+1\right)-y^2=\left(2x+1\right)^2-y^2=\left(2x+1+y\right).\left(2x+1-y\right)\)
b ) \(x^3-x+y^3-y\)
= \(\left(x^3+y^3\right)-\left(x+y\right)\)
= \(\left(x+y\right)\left(x^2-xy+y^2\right)-\left(x+y\right)\)
= \(\left(x+y\right)\left(x^2-xy+y^2-1\right)\)
Chúc bạn học tốt !!!
\(a.\)\(4x^2-y^2+4x+1\)
\(=\left(4x^2+4x+1\right)-y^2\)
\(=\left(2x+1\right)^2-y^2\)
\(=\left(2x+1+y\right)\left(2x+1-y\right)\)
Trả lời:
a, 5x2 + 10xy + 5y2 = 5 ( x2 + 2xy + y2 ) = 5 ( x + y )2
b, x2 + 3x - y2 + 3y = ( x2 - y2 ) + ( 3x + 3y ) = ( x - y )( x + y ) + 3 ( x + y ) = ( x + y )( x - y + 3 )
c, x2 + 5x - y2 + 5y = ( x2 - y2 ) + ( 5x + 5y ) = ( x - y )( x + y ) + 5 ( x + y ) = ( x + y )( x - y + 5 )
d, 3x2 - 3y2 - 2 ( x - y )2 = 3 ( x2 - y2 ) - 2 ( x - y )2 = 3 ( x - y )( x + y ) - 2 ( x - y )2 = ( x - y )[ 3 ( x + y ) - 2 ] = ( x - y )( 3x + 3y - 2 )
e, x2 - 2x - 4y2 - 4y = ( x2 - 4y2 ) - ( 2x + 4y ) = ( x - 2y )( x + 2y ) - 2 ( x + 2y ) = ( x + 2y )( x - 2y - 2 )
a) 5x2+10xy+5y2
=5(x2+2xy+y2)
=5(x+y)2
b) x2+3x-y2+3y
=(x2-y2)+(3x+3y)
=(x-y)(x+y)+3(x+y)
=(x+y)(x-y+3)
c) x2+5x-y2+5y
=(x2-y2)+(5x+5y)
=(x-y)(x+y)+5(x+y)
=(x+y)(x-y+5)
d) 3x2-3y2-2(x-y)2
=3(x2-y2)-2(x-y)2
=3(x-y)(x+y)-2(x-y)2
=(x-y)[3(x+y)-2(x-y)]
e) x2-2x-4y2-4y
=(x2-4y2)-(2x+4y)
=(x-2y)(x+2y)-2(x+2y)
=(x+2y)(x-2y-2)
#H
a ) \(3x^2-7x+2\)
= \(3x^2-6x-x+2\)
= \(3x\left(x-2\right)-\left(x-2\right)\)
= \(\left(x-2\right)\left(3x-1\right)\)
b ) \(a\left(x^2+1\right)-x\left(a^2+1\right)\)
= \(ax\left(x-a\right)-\left(x-a\right)\)
= \(\left(x-a\right)\left(ax-1\right)\)
Chúc bạn học tốt !!!
\(a^2-2ab+b^2-c^2\)
\(=\left(a-b\right)^2-c^2\)
\(=\left(a-b+c\right)\left(a-b-c\right)\)